2′-Fucosyllactose mitigates cognitive deficits in Alzheimer models: targeting amyloid pathology, oxidative stress, and synaptic plasticity - Munni, Yeasmin Akter; Tran, Khoa Nguyen; Jeon, Seon-Min; Hwang, Meeyul; Yoon, Jong-Won; Song, Young-Ha; Oh, Tae Woo; Gum, Sang Il; Yang, In-Jun (Frontiers in Pharmacology, 2025)
IntroductionThe development of new drugs for Alzheimer’s disease (AD) remains a major challenge due to the disorder’s complex and multifactorial nature. 2′-Fucosyllactose (2′-FL), a human milk oligosaccharide, has demonstrated promising neuroprotective properties. However, its effects on AD-related cognitive decline are not yet fully understood. This study aimed to investigate the therapeutic potential of 2′-FL in an aging mouse model of AD and to explore the underlying mechanisms involved.Methods5xFAD transgenic mice were treated with 2′-FL and assessed for cognitive function using the Morris water maze and Y-maze tests. Immunohistochemical staining was used to evaluate amyloid-beta (Aβ) and phosphorylated tau (p-tau) levels in brain tissue samples. Blood samples were analyzed to determine circulating cytokine levels. Additionally, BV2 microglial cells and primary hippocampal neurons (PHNs) were used in vitro to investigate the effects of 2′-FL on neuroinflammation, oxidative stress, and synaptic plasticity.Results2′-FL (300–1,200 mg/kg, oral) improved cognitive performance in 5xFAD mice by shortening escape latency in the water maze and restoring alternation behavior in the Y-maze test. It significantly reduced Aβ plaque load in the hippocampus and cortex but did not significantly affect tau hyperphosphorylation. Furthermore, 2′-FL lowered plasma tumor necrosis factor (TNF)-α and interleukin (IL)-6 levels. In BV2 cells, it suppressed d-galactose-induced neuroinflammation by downregulating TNF-α and IL-6, and nuclear factor-κB signaling. In PHNs, 2′-FL reduced oxidative stress, restored mitochondrial function, and limited DNA damage. Additionally, it counteracted d-galactose-induced synaptic deficits by promoting neurite outgrowth, enhancing synaptic vesicle recycling, and upregulating the synaptic markers brain-derived neurotrophic factor, postsynaptic density protein-95, and synaptic vesicle protein 2.Conclusion2′-FL improved cognitive performance in 5xFAD mice, reduced Aβ plaque deposition and pro-inflammatory cytokine levels in vivo, and mitigated oxidative stress and synaptic dysfunction in cellular models. These findings indicate that 2′-FL modulates multiple pathological features relevant to AD in preclinical models.